Automatic tablet cooler / Muhamad Hazim Lokman & Noor Azrin Ahmad Nazri - Lokman, Muhamad Hazim; Nazri, Noor Azrin (2015)
Faculty of Electrical Engineering from University Teknologi Mara (UiTM) has given a task to electrical engineering student to do Final Year Project in order to achieved Diploma of Electrical Engineering. The Final Year Project requires student to develop new idea and come out with a fresh invention. Generally, this thesis will show the procedure and the process of making the Final Year Project. The project known as "Automatic Tablet Cooler", which helps the user of the smart tablet prevent their gadget from overheating and make the lifespan of that tablet longer. The objectives, problem statements and the result also shown in this thesis. This thesis also will show the problem faced during the making of the project, the troubleshooting process and the conclusion of this Final Year Project. The purpose of Final Year Project is to learn about how to work as a team and invent something that can solve any problem occurred.